Quantitative Analysis within Language Studies: An Analytical Views Based on the Bibliometrics Method - Nugraha, Danang Satria (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Abstract Background: While qualitative research methods have provided insights into linguistic structures and processes, the recent decades have witnessed a growing emphasis on quantitative approaches. Methodology: This study utilizes a bibliometric analysis based on the PRISMA guidelines to explore research trends in “Quantitative Analysis within Language Studies” from 2014 to 2024 by analyzing the metadata of 53,575 journal articles retrieved from a reputable database, i.e., Dimensions. Findings: The findings show that (1) there was a steady rise in publications throughout the period; (2) the total citations increased by over 113,000, representing a nearly 100-fold growth (1,141 citations in 2014 compared to 41,203 citations in 2024); (3) according to the ANZSRC 2020 classification, the field of Language, Communication and Culture has the highest number of publications (53,575), followed by Linguistics (32,121) and Language Studies (18,272); (4) there was the top 10 journals from 2014 to 2024; (5) there was a detail into the publication productivity and citation impact of 20 leading researchers; and (6) it has been extracted 1,028 terms concerning the examined query that classified into eight clusters. Conclusion: By integrating the insights gleaned from publication trends, citation analysis, leading authors, journal distribution, map-based visualizations, and cluster analysis of terms, this study provides a comprehensive and detailed picture of research trends within the search query. Originality: While current several research in quantitative language studies tends to delve into specific subfields, offering piecemeal understandings of the overall landscape, this study takes a distinct approach. By examining 53,575 articles content and metadata, this study aims to provide a more comprehensive perspective compare to previous fragmented insights.